Environment-friendly PUR hot melt adhesive with excellent temperature resistance as well as preparation method and application of environment-friendly PUR hot melt adhesive

By improving the polyester polyol and isocyanate formula and adding aging-resistant additives to form a high crosslink density structure, the problem of insufficient heat resistance and thermal cycle stability of polyurethane hot melt adhesive at high temperatures is solved, and good results are achieved at high temperatures Adhesion and flexibility.

CN119264867AInactive Publication Date: 2025-01-07DONGGUAN APUBOND NEW MATERIAL TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411587934.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Polyurethane hot melt adhesive has poor heat resistance and thermal cycle stability in high temperature environments, making it difficult to maintain bonding performance for a long time.

Method used

Using improved polyester polyol and modified isocyanate formulations, cinnamic acid, chlorogenic acid and tannin to improve the heat resistance of hot melt adhesives, and using nano-inorganic oxides as aging-resistant additives to form high cross-linking density Network structure to enhance thermal stability.

Benefits of technology

It significantly improves the heat resistance and thermal cycle stability of PUR hot melt adhesive, ensures good adhesion and flexibility in high temperature environments, and avoids the performance of hot melt adhesives in long-term use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005124761170000021
    Figure BDA0005124761170000021
  • Figure BDA0005124761170000071
    Figure BDA0005124761170000071
  • Figure BDA0005124761170000091
    Figure BDA0005124761170000091
Patent Text Reader

Abstract

The invention provides an environment-friendly PUR hot melt adhesive with excellent temperature resistance as well as a preparation method and application thereof, and belongs to the technical field of adhesives. The environment-friendly PUR hot melt adhesive is prepared from the following raw materials in parts by mass: 50 to 65 parts of polyester polyol, 10 to 20 parts of polyether polyol, 15 to 30 parts of isocyanate, 5 to 10 parts of modified isocyanate, 5 to 10 parts of chain extender and 3 to 5 parts of anti-aging additive, wherein the polyester polyol is formed by carrying out dehydration polycondensation on polybasic acid and polyol through a vacuum melting method, and the polybasic acid comprises binary acid, cinnamic acid, chlorogenic acid and tannic acid according to the mass ratio of (3-5): (0.5-0.8): (1.2-1.6): 1; the anti-aging auxiliary agent is a nano inorganic oxide containing a maleimide group; the modified isocyanate is a mixture obtained by reacting polyisocyanate, sulfamic acid, hydroxycarboxylic acid and tertiary amine. The PUR hot melt adhesive prepared by the invention has excellent thermal stability, and the cohesiveness of the PUR hot melt adhesive can be kept basically unchanged in a long-term high-temperature environment and a thermal cycle environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adhesives, and in particular relates to an environmentally friendly PUR hot melt adhesive with excellent heat resistance, and a preparation method and application thereof. Background Art

[0002] Hot melt adhesive is a thermoplastic resin that becomes liquid when heated, hardens and forms a bond after cooling. It usually exists in solid form. When heated to a certain temperature, it melts into a fluid state and can be applied or sprayed onto the material to be bonded. Hot melt adhesives are divided into EVA (ethylene-vinyl acetate copolymer) hot melt adhesives, PVC (polyvinyl chloride) hot melt adhesives, PUR (polyurethane) hot melt adhesives and PA (polyamide) hot melt adhesives according to their chemical composition. Each hot melt adhesive has corresponding advantages and disadvantages.

[0003] Polyurethane hot melt adhesive is a thermoplastic resin composed of polyurethane prepolymer and chain extender. It has the advantages of high-strength bonding, good flexibility, excellent chemical resistance and fast curing. It is used in many fields such as automotive industry, furniture manufacturing, construction, electronic products and packaging industry. However, in actual application, although polyurethane hot melt adhesive has many advantages, it still has some limitations in some high-temperature environments.

[0004] In order to solve the problem of the degradation of various properties of the above-mentioned polyurethane hot melt adhesive at high temperatures, inorganic fillers can be added to the formula of the polyurethane hot melt adhesive, polyisocyanates with high heat resistance can be selected, and compounding with epoxy resin or phenolic resin can be performed. However, it is found that these methods can only improve the heat resistance of the polyurethane hot melt adhesive in the short term, and the long-term heat resistance and thermal cycle stability are still poor. Summary of the invention

[0005] The purpose of the present invention is to provide an environmentally friendly PUR hot melt adhesive with excellent temperature resistance and a preparation method and application thereof, so as to solve the problem that the long-term heat resistance and thermal cycle stability of the above-mentioned polyurethane hot melt adhesive are poor.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] The first aspect of the present invention provides an environmentally friendly PUR hot melt adhesive with excellent temperature resistance. The environmentally friendly PUR hot melt adhesive comprises the following raw materials in parts by weight:

[0008]

[0009] The polyester polyol is prepared by dehydration polycondensation of polyacids and polyols by vacuum melting method, and the polyacids include dibasic acid, cinnamic acid, chlorogenic acid and tannic acid in a mass ratio of (3-5): (0.5-0.8): (1.2-1.6): 1;

[0010] The anti-aging additive is a nano inorganic oxide containing maleimide groups;

[0011] The modified isocyanate is a mixture obtained by reacting polyisocyanate, aminosulfonic acid, hydroxycarboxylic acid and tertiary amine.

[0012] As the application field of PUR hot melt adhesive becomes wider and wider, the requirements for PUR hot melt adhesive are also getting higher and higher, especially in terms of heat resistance. In view of this problem, the present invention improves the polyacid in the polyester polyol reaction process, not only adding dibasic organic acids such as azelaic acid, sebacic acid, and terephthalic acid in the prior art, but also adding cinnamic acid, chlorogenic acid and tannic acid, which significantly improves the heat resistance of the hot melt adhesive. Analysis of the reasons: Cinnamic acid is an organic acid with a conjugated double bond structure. The conjugated double bonds in its molecules can form stable free radical intermediates at high temperatures. These free radical intermediates can capture other free radicals that may cause thermal degradation, thereby delaying or preventing the thermal degradation process. Chlorogenic acid is a naturally occurring polyphenol compound with strong antioxidant properties. It can capture free radicals by providing hydrogen atoms or electrons to prevent chain reactions caused by free radicals, thereby reducing the thermal degradation of polymers. Tannic acid is a complex polyphenol compound containing multiple phenolic hydroxyl groups, which can form hydrogen bonds or covalent bonds with active sites on polymer chains, enhance the interaction between polymer chains, and improve the cohesion and heat resistance of hot melt adhesives. In the present invention, cinnamic acid, chlorogenic acid and tannic acid all contain multiple functional groups (such as carboxyl groups, phenolic hydroxyl groups, etc.), which can react with polyols and isocyanates to form more crosslinking points. Increasing the crosslinking density can improve the stability of the polymer network, thereby enhancing the adhesion of the hot melt adhesive at high temperatures.

[0013] Preferably, the dibasic acid is at least one of azelaic acid, sebacic acid, terephthalic acid, and succinic acid; and the polyol is at least one of hexanediol, 1,3-butanediol, 1,4-cyclohexanedimethanol, pentaerythritol, and diethylene glycol.

[0014] Preferably, the preparation method of polyester polyol is:

[0015] The polyacid and the polyol are mixed in a mass ratio of (1-3):1, and an esterification reaction is carried out at 150-180°C for 1-3 hours, and then cooled to room temperature to obtain a polyester polyol.

[0016] Preferably, the polyether polyol is at least one of tetrahydrofuran-propylene oxide copolymer glycol and polytetrahydrofuran ether glycol.

[0017] Preferably, the isocyanate is at least one of diphenylmethane diisocyanate and hexamethylene diisocyanate.

[0018] Preferably, the preparation method of the modified isocyanate is:

[0019] According to parts by mass, 350-400 parts of polyisocyanate, 10-12 parts of aminosulfonic acid, 0.15-0.2 parts of hydroxycarboxylic acid and 5-10 parts of tertiary amine are mixed, and reacted at 75-85° C. for 4-6 hours under nitrogen protection to convert into a clear modified isocyanate mixture;

[0020] The polyisocyanate is at least one of toluene diisocyanate, isophorone diisocyanate and triphenylmethane triisocyanate;

[0021] The aminosulfonic acid is at least one of 3-(cyclohexylamino)-1-propanesulfonic acid and 4-(cyclohexylamino)-1-butanesulfonic acid;

[0022] The hydroxycarboxylic acid is at least one of 12-hydroxyoctadecanoic acid and 10-hydroxystearic acid;

[0023] The tertiary amine is at least one of N,N-dimethylcyclohexylamine and N-methylpiperidine.

[0024] Preferably, the chain extender is at least one of ethylene glycol, propylene glycol, 1,3-succinic acid, and 1,4-cyclohexanedimethanol.

[0025] In order to further optimize the heat resistance of the hot melt adhesive, modified isocyanate is also added in the present invention to further improve the heat resistance of the PUR hot melt adhesive. Analysis of the reasons: The reaction of polyisocyanate with aminosulfonic acid, hydroxycarboxylic acid and tertiary amine can generate modified isocyanate with more active functional groups. These active functional groups can form more cross-linking points in the subsequent hot melt adhesive preparation process, thereby increasing the cross-linking density of the polymer network. The high cross-linking density network structure is more stable during the thermal cycle process. During repeated heating and cooling, the high cross-linking density network structure can reduce the relaxation and rearrangement of the polymer chain, thereby improving the long-term thermal stability and thermal cycle stability of the PUR hot melt adhesive.

[0026] Preferably, the preparation method of the anti-aging additive is:

[0027] Cerium dioxide, titanium dioxide and zinc oxide are mixed to obtain a mixture, wherein the mass ratio of cerium dioxide, titanium dioxide and zinc oxide is (3-5):(0.8-1.2):1, the mixture is added into a hydrochloric acid solution with a mass concentration of 1-3%, ground in a ball mill for 2-4 hours, filtered and dried to obtain an activated mixture;

[0028] The activated mixture is mixed with N-(2-aminoethyl)-3-aminopropyltrimethoxysilane and ethanol, wherein the mass ratio of the activated mixture, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane and ethanol is 1:(0.03-0.05):(5-10), reacted at 40-50° C. for 3-5 hours, filtered and dried to obtain a modified mixture;

[0029] According to parts by mass, 5 to 10 parts of the modified mixture, 40 to 50 parts of maleimide monomer and 40 to 50 parts of bisphenol A epoxy resin are dissolved in 100 to 120 parts of butanone, reacted at 110 to 150° C. for 2 to 5 hours, and the butanone was evaporated under reduced pressure at 60 to 80° C. to obtain an anti-aging additive;

[0030] The maleimide monomer is at least two of N-phenylmaleimide, N-(2-methylphenyl)maleimide, N-(4-methylphenyl)maleimide, N-(2,6-dimethylphenyl)maleimide, bis(4-maleimidophenyl)methane, and 2,2-bis(4-(4-maleimidophenoxy)-phenyl)propane.

[0031] The present invention continues to develop and find that although the addition of cinnamic acid, chlorogenic acid and tannic acid can further improve the heat resistance of the hot melt adhesive, this heat resistance is maintained for a short time. If the hot melt adhesive is in a high temperature environment for a long time, the adhesiveness will be significantly reduced. At the same time, the adhesiveness will also be reduced during the high and low temperature cycle. In response to this problem, the present invention adds an anti-aging additive of a specific composition to solve the problem of poor long-term heat resistance and poor thermal cycle stability of the hot melt adhesive. Analysis of the reasons: The nano-inorganic oxides in the anti-aging additives have a high specific surface area and surface activity, which enables them to be evenly dispersed in the polymer matrix to form a stable nano-composite material. These nanoparticles can act as a physical barrier to hinder the transfer of heat, thereby reducing the occurrence of thermal degradation. In addition, the presence of nano-inorganic oxides can improve the stability of the hot melt adhesive during the thermal cycle. During repeated heating and cooling, the nanoparticles can act as physical support points to reduce the relaxation and rearrangement of the polymer chains, thereby maintaining the structural integrity of the hot melt adhesive, and then keeping the adhesiveness of the hot melt adhesive basically unchanged. The maleimide groups in the anti-aging additive can form covalent bonds or hydrogen bonds with the polymer chains, enhancing the cross-linking density of the polymer chains and improving the thermal stability of the hot melt adhesive. This enhanced cross-linking structure makes it more difficult for the hot melt adhesive to soften and flow at high temperatures, maintaining good adhesion. In addition, the cross-linking structure between the maleimide groups and the polymer chains is more stable during the thermal cycle process, which can resist the stress and strain caused by temperature changes and reduce the performance degradation of the hot melt adhesive.

[0032] The second aspect of the present invention provides a method for preparing an environmentally friendly PUR hot melt adhesive with excellent temperature resistance, comprising the following steps:

[0033] (1) mixing polyester polyol, polyether polyol, isocyanate, modified isocyanate, chain extender and anti-aging additive uniformly, conveying to a twin-screw extruder for heating reaction, the temperature of the twin-screw extruder is 220-250° C., and granulating in water, the temperature of the water is 5-15° C., to obtain polyurethane granules;

[0034] (2) Drying the polyurethane rubber particles at 70-80° C. to obtain PUR hot melt adhesive.

[0035] The third aspect of the present invention provides an application of an environmentally friendly PUR hot melt adhesive with excellent temperature resistance, and the application of the PUR hot melt adhesive in the automotive industry, furniture manufacturing, electronic products, packaging products, textiles and clothing, and medical equipment.

[0036] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0037] 1. The use of isocyanate and modified isocyanate in the present invention increases the crosslinking density of the polyurethane network structure, so that the PUR hot melt adhesive can still maintain good adhesion at high temperatures.

[0038] 2. The present invention also adds specific anti-aging additives, which contain maleimide groups and nano inorganic oxides. These substances can significantly improve the antioxidant and thermal degradation resistance of the PUR hot melt adhesive, so that it can still maintain good adhesion in a long-term high-temperature environment.

[0039] 3. The combined use of polyester polyol and polyether polyol in the present invention gives the PUR hot melt adhesive good flexibility and elasticity. The synergistic effect of the two polyols enables the hot melt adhesive to maintain good bonding performance after multiple thermal cycles without obvious performance degradation. DETAILED DESCRIPTION

[0040] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] Example 1

[0042] This embodiment provides an environmentally friendly PUR hot melt adhesive with excellent temperature resistance, which includes the following raw materials in parts by mass:

[0043]

[0044] The polyether polyol is polytetramethylene ether glycol (CAS: 25190-06-1); the isocyanate is hexamethylene diisocyanate (CAS: 822-06-0); the chain extender is 1,2-propylene glycol (CAS: 57-55-6);

[0045] The preparation method of polyester polyol is:

[0046] The polyacid and the polyol are mixed, the polyacid includes a dibasic acid, cinnamic acid (CAS: 140-10-3), chlorogenic acid (CAS: 327-97-9) and tannic acid (CAS: 1401-55-4) in a mass ratio of 3: 0.6: 1.2: 1, the dibasic acid is sebacic acid, the polyol is 1,4-cyclohexanedimethanol (CAS: 105-08-8), the mass ratio of the polyacid to the polyol is 2.5: 1, and an esterification reaction is carried out at 175° C. for 1 hour, and then cooled to room temperature to obtain a polyester polyol.

[0047] The preparation method of modified isocyanate is:

[0048] According to the mass parts, 380 parts of polyisocyanate, 12 parts of aminosulfonic acid, 0.2 parts of hydroxycarboxylic acid and 6 parts of tertiary amine were mixed, and reacted at 85° C. for 4 hours under nitrogen protection to convert into a clear modified isocyanate mixture;

[0049] The polyisocyanate is isophorone diisocyanate (CAS: 4098-71-9);

[0050] Aminosulfonic acid is 4-(cyclohexylamino)-1-butanesulfonic acid (CAS: 161308-34-5);

[0051] The hydroxycarboxylic acid is 10-hydroxystearic acid (CAS: 638-26-6);

[0052] The tertiary amine is N-methylpiperidine (CAS: 626-67-5).

[0053] The preparation method of the anti-aging additive is:

[0054] Cerium dioxide, titanium dioxide and zinc oxide are mixed to obtain a mixture, wherein the mass ratio of cerium dioxide, titanium dioxide and zinc oxide is 3:1.2:1, the mixture is added into a hydrochloric acid solution with a mass concentration of 2.5%, and the mass volume ratio of the mixture to the hydrochloric acid solution is 1 g:10 mL, and the mixture is ground in a ball mill for 2 hours, filtered and dried to obtain an activated mixture;

[0055] Cerium dioxide, titanium dioxide and zinc oxide were purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., with models of XFI65, XFI02 and XFI06 respectively. The particle size of cerium dioxide was 40-55 nm, the particle size of titanium dioxide was 20-40 nm, and the particle size of zinc oxide was 30-80 nm.

[0056] The activated mixture was mixed with N-(2-aminoethyl)-3-aminopropyltrimethoxysilane (CAS: 1760-24-3) and ethanol, wherein the mass ratio of the activated mixture, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane and ethanol was 1:0.05:6, and the mixture was reacted at 50° C. for 3 h, filtered and dried to obtain a modified mixture;

[0057] According to the mass parts, 5 parts of the modified mixture, 40 parts of maleimide monomer and 50 parts of bisphenol A epoxy resin (purchased from Guangzhou Kailuwei Chemical Co., Ltd., brand E-44) were dissolved in 100 parts of butanone, reacted at 120°C for 2h, and the butanone was evaporated under reduced pressure at 65°C to obtain an anti-aging additive;

[0058] The maleimide monomer is N-(2,6-dimethylphenyl)maleimide (CAS: 1206-49-1) and di(4-maleimidophenyl)methane (CAS: 13676-54-5), and the mass ratio of the two is 1:1.

[0059] A method for preparing an environmentally friendly PUR hot melt adhesive with excellent temperature resistance comprises the following steps:

[0060] (1) mixing polyester polyol, polyether polyol, isocyanate, modified isocyanate, chain extender and anti-aging additive uniformly, conveying to a twin-screw extruder for heating reaction, the temperature of the twin-screw extruder is 230° C., and granulating in water, the temperature of the water is 10° C., to obtain polyurethane granules;

[0061] (2) Drying the polyurethane rubber particles at 75° C. to obtain PUR hot melt adhesive.

[0062] Example 2

[0063] This embodiment provides an environmentally friendly PUR hot melt adhesive with excellent temperature resistance, which includes the following raw materials in parts by mass:

[0064]

[0065] The polyether polyol is polytetramethylene ether glycol (CAS: 25190-06-1); the isocyanate is diphenylmethane diisocyanate (CAS: 101-68-8); the chain extender is ethylene glycol;

[0066] The preparation method of polyester polyol is:

[0067] The polyacid and the polyol are mixed, the polyacid includes a dibasic acid, cinnamic acid (CAS: 140-10-3), chlorogenic acid (CAS: 327-97-9) and tannic acid (CAS: 1401-55-4) in a mass ratio of 4:0.6:1.4:1, the dibasic acid is azelaic acid, the polyol is 1,4-cyclohexanedimethanol, the mass ratio of the polyacid to the polyol is 1.5:1, and an esterification reaction is carried out at 165°C for 2 hours, and then cooled to room temperature to obtain a polyester polyol.

[0068] The preparation method of modified isocyanate is:

[0069] According to parts by mass, 380 parts of polyisocyanate, 11 parts of aminosulfonic acid, 0.18 parts of hydroxycarboxylic acid and 6 parts of tertiary amine were mixed, reacted at 80° C. for 5 hours under nitrogen protection, and converted into a clear modified isocyanate mixture;

[0070] The polyisocyanate is toluene diisocyanate (CAS: 584-84-9);

[0071] Aminosulfonic acid is 3-(cyclohexylamino)-1-propanesulfonic acid (CAS: 113-40-6);

[0072] The hydroxycarboxylic acid is 12-hydroxyoctadecanoic acid (CAS: 106-14-9);

[0073] The tertiary amine is N,N-dimethylcyclohexylamine (CAS: 98-94-2).

[0074] The preparation method of the anti-aging additive is:

[0075] Cerium dioxide, titanium dioxide and zinc oxide are mixed to obtain a mixture, wherein the mass ratio of cerium dioxide, titanium dioxide and zinc oxide is 4:1:1, the mixture is added into a hydrochloric acid solution with a mass concentration of 2%, and the mass volume ratio of the mixture to the hydrochloric acid solution is 1 g:10 mL, the mixture is ground in a ball mill for 3 hours, and an activated mixture is obtained after filtering and drying;

[0076] Cerium dioxide, titanium dioxide and zinc oxide were purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., with models of XFI65, XFI02 and XFI06 respectively. The particle size of cerium dioxide was 40-55 nm, the particle size of titanium dioxide was 20-40 nm, and the particle size of zinc oxide was 30-80 nm.

[0077] The activated mixture was mixed with N-(2-aminoethyl)-3-aminopropyltrimethoxysilane (CAS: 1760-24-3) and ethanol, wherein the mass ratio of the activated mixture, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane and ethanol was 1:0.04:6, and the mixture was reacted at 45° C. for 4 hours, filtered and dried to obtain a modified mixture;

[0078] According to the mass parts, 8 parts of the modified mixture, 45 parts of maleimide monomer and 45 parts of bisphenol A epoxy resin (purchased from Guangzhou Kailuwei Chemical Co., Ltd., brand E-44) were dissolved in 110 parts of butanone, reacted at 120°C for 2h, and the butanone was evaporated under reduced pressure at 70°C to obtain an anti-aging additive;

[0079] The maleimide monomers are N-phenylmaleimide (CAS: 941-69-5) and N-(2-methylphenyl)maleimide (CAS: 4067-01-0), and the mass ratio of the two is 1:1.

[0080] A method for preparing an environmentally friendly PUR hot melt adhesive with excellent temperature resistance comprises the following steps:

[0081] (1) mixing polyester polyol, polyether polyol, isocyanate, modified isocyanate, chain extender and anti-aging additive uniformly, conveying to a twin-screw extruder for heating reaction, the temperature of the twin-screw extruder is 245° C., and granulating in water, the temperature of the water is 8° C., to obtain polyurethane granules;

[0082] (2) Drying the polyurethane rubber particles at 80° C. to obtain PUR hot melt adhesive.

[0083] Comparative Example 1

[0084] The difference between this comparative example and Example 1 is that the mass ratio of the polyacid in the polyester polyol is different. The polyacid in this comparative example includes dibasic acid, cinnamic acid, chlorogenic acid and tannic acid in a mass ratio of 3:2:1.2:1.

[0085] Comparative Example 2

[0086] The difference between this comparative example and Example 1 is that the types of polyacids in the polyester polyol are different, and the polyacid used in this comparative example is azelaic acid.

[0087] Comparative Example 3

[0088] The difference between this comparative example and Example 1 is that the types of modified isocyanate are different. In this comparative example, the modified isocyanate is replaced by isophorone diisocyanate.

[0089] Comparative Example 4

[0090] The difference between this comparative example and Example 1 is that the addition ratio of the raw materials in the modified isocyanate is different. The preparation method of the modified isocyanate in this comparative example is:

[0091] According to parts by mass, 380 parts of polyisocyanate, 30 parts of aminosulfonic acid, 1 part of hydroxycarboxylic acid and 15 parts of tertiary amine were mixed, reacted at 85° C. for 4 hours under nitrogen protection, and then converted into a clear modified isocyanate mixture.

[0092] Comparative Example 5

[0093] The difference between this comparative example and Example 1 is that no modified isocyanate is added, and in this comparative example, the modified isocyanate is replaced by hexamethylene diisocyanate.

[0094] Comparative Example 6

[0095] The difference between this comparative example and Example 1 is that the types of the anti-aging additives are different. In this comparative example, the modified mixture is directly added as the anti-aging additive into the preparation process of the PUR hot melt adhesive.

[0096] Comparative Example 7

[0097] The difference between this comparative example and Example 1 is that the type of anti-aging additive is different, and the amino-containing silane coupling agent is not modified. The preparation method of the anti-aging additive in this comparative example is:

[0098] Cerium dioxide, titanium dioxide and zinc oxide are mixed to obtain a mixture, wherein the mass ratio of cerium dioxide, titanium dioxide and zinc oxide is 3:1.2:1, the mixture is added into a hydrochloric acid solution with a mass concentration of 2.5%, ground in a ball mill for 2 hours, filtered and dried to obtain an activated mixture;

[0099] According to the mass parts, 5 parts of the activated mixture, 40 parts of maleimide monomer and 50 parts of bisphenol A epoxy resin were dissolved in 100 parts of butanone, reacted at 120°C for 2 hours, and the butanone was evaporated under reduced pressure at 65°C to obtain an anti-aging additive;

[0100] The maleimide monomer is N-(2,6-dimethylphenyl)maleimide and di(4-maleimidophenyl)methane, and the mass ratio of the two is 1:1.

[0101] Comparative Example 8

[0102] The difference between this comparative example and Example 1 is that the mass ratio of the nano inorganic oxides in the anti-aging additive is different. In this comparative example, the mass ratio of cerium dioxide, titanium dioxide and zinc oxide is 3:3:1.

[0103] Performance Testing

[0104] The PUR hot melt adhesive prepared in each embodiment and comparative example was heated and melted, and then coated on two metal plates with smooth surfaces to obtain bonding specimens.

[0105] Heat resistance test: After the bonding specimens are cured for 7 days, they are placed in a constant temperature oven with an initial temperature of 25°C and heated at a rate of 20°C / h. Check every 15 minutes to see if the bonding specimens are loose. If they are loose, record the temperature at that time and record it as the heat resistance temperature.

[0106] Initial bonding strength test: The compression shear strength test is carried out after the bonding specimen is cured for 10 minutes. The test process is carried out in accordance with QJ1634A-96 "Adhesive Compression Shear Strength Test Method".

[0107] Final bonding strength test: The compression shear strength test is carried out after the bonding specimens are cured for 7 days. The test process is carried out in accordance with QJ1634A-96 "Adhesive Compression Shear Strength Test Method".

[0108] Long-term heat resistance test: After the bonding specimens were cured for 7 days, they were placed in a constant temperature oven at 80°C for 10 days, taken out, and subjected to a compression shear strength test. The test process was carried out in accordance with QJ 1634A-96 "Adhesive Compression Shear Strength Test Method". The shear strength results of the long-term heat resistance test were combined with the shear strength results of the final adhesion strength test to calculate the shear strength attenuation rate. The calculation formula is: shear strength attenuation rate = (shear strength of the final adhesion strength test - shear strength of the long-term heat resistance test) / shear strength of the final adhesion strength test.

[0109] Thermal cycle stability performance test: After curing for 7 days, the bonded specimens were placed in a constant temperature oven at 80°C for 1 day, taken out, cooled to room temperature, placed at room temperature for 1 day, and then placed in a constant temperature oven at 80°C for 1 day. This cycle was repeated 10 times, and finally a compression shear strength test was performed. The test process was carried out in accordance with QJ 1634A-96 "Adhesive Compression Shear Strength Test Method". The shear strength results of the thermal cycle stability performance test and the shear strength results of the final adhesion strength test were used to calculate the shear strength attenuation rate. The calculation formula is: shear strength attenuation rate = (shear strength of the final adhesion strength test - shear strength of the thermal cycle stability performance test) / shear strength of the final adhesion strength test. The performance test results are shown in Table 1.

[0110] Table 1 Performance test results

[0111]

[0112]

[0113] It can be seen from the above performance test results that the hot melt adhesives of Examples 1-2 have excellent heat resistance, especially Example 2 has the most outstanding comprehensive performance. This is mainly because specific polyester polyols, modified isocyanates and anti-aging additives are added to the raw materials of the hot melt adhesive, which react with other raw materials to form a higher cross-linking density, thereby improving the heat resistance of the hot melt adhesive.

[0114] However, the comparative examples are significantly worse than the examples in terms of corresponding performance tests because they do not adopt the necessary technical solutions. In comparative example 1, the mass ratio of the polyacid in the polyester polyol is changed. From the results, it can be seen that the heat resistance of the hot melt adhesive decreases, proving that the mass ratio of the polyacid has an important influence on the heat resistance. In comparative example 2, the type of polyacid is further changed. Cinnamic acid, chlorogenic acid and tannic acid are not used. Only azelaic acid is used as a polyacid to react with the polyol. From the results, it can be seen that the heat resistance is further reduced, indicating that the type of polyacid is limited in the present invention, which can improve the heat resistance of the hot melt adhesive. In comparative example 3, the isocyanate is not modified, but isophorone diisocyanate is directly added to the preparation process of the hot melt adhesive. From the results, it can be seen that the heat resistance of the hot melt adhesive prepared therefrom decreases, especially the long-term heat resistance and thermal cycle stability performance decrease significantly, indicating the necessity of adding modified isocyanate in the present invention. In Comparative Example 4, the addition ratio of each raw material in the preparation process of the modified isocyanate was changed. From the results, it can be seen that it has a certain degree of influence on the heat resistance of the hot melt adhesive, indicating that the preparation process of the modified isocyanate in the present invention is specific and has an influence on the heat resistance of the hot melt adhesive. In Comparative Example 5, no modified isocyanate was added, but an equal mass of isocyanate was added. From the results, it can be seen that this has a more obvious effect on the heat resistance of the hot melt adhesive, indicating that the modified isocyanate and isocyanate in the present invention have a synergistic effect, jointly participate in the preparation of the hot melt adhesive, and improve the crosslinking density of the hot melt adhesive. In Comparative Example 6, the nano inorganic oxide was not modified with maleimide groups, and the nano inorganic oxide modified with silane coupling agent was directly added to the preparation process of hot melt adhesive. From the results, it can be seen that the heat resistance of the hot melt adhesive was significantly reduced, indicating that the anti-aging additive in the present invention was first activated and modified with silane coupling agent, and then modified with maleimide group. Both modification processes are indispensable, indicating that the anti-aging additive has an important influence on the improvement of the heat resistance of the hot melt adhesive of the present invention. In Comparative Example 7, only the nano inorganic oxide in the anti-aging additive was acid activated, no specific silane coupling agent was added, and then reacted with maleimide monomer and epoxy resin. From the results, it can be seen that the heat resistance of the hot melt adhesive was reduced to a certain extent, indicating that the multi-step modification of the nano inorganic oxide in the present invention has an important influence on improving the heat resistance of the hot melt adhesive. In Comparative Example 8, the mass ratios of various nano inorganic oxides were changed. From the results, it can be seen that the heat resistance of the hot melt adhesive decreased to a certain extent, indicating that the mass ratio of the nano inorganic oxides will affect its distribution in the hot melt adhesive, thereby affecting the overall performance of the hot melt adhesive. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effect.

[0115] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. An environmentally friendly PUR hot melt adhesive with excellent temperature resistance, characterized in that: Environmentally friendly PUR hot melt adhesive includes the following raw materials by weight: The polyester polyol is prepared by dehydration polycondensation of polyacids and polyols by vacuum melting method, and the polyacids include dibasic acid, cinnamic acid, chlorogenic acid and tannic acid in a mass ratio of (3-5): (0.5-0.8): (1.2-1.6): 1; The anti-aging additive is a nano inorganic oxide containing maleimide groups; The modified isocyanate is a mixture obtained by reacting polyisocyanate, aminosulfonic acid, hydroxycarboxylic acid and tertiary amine.

2. The environmentally friendly PUR hot melt adhesive with excellent temperature resistance according to claim 1, characterized in that: The dibasic acid is at least one of azelaic acid, sebacic acid, terephthalic acid, and succinic acid; the polyol is at least one of hexanediol, 1,3-butanediol, 1,4-cyclohexanedimethanol, pentaerythritol, and diethylene glycol.

3. The environmentally friendly PUR hot melt adhesive with excellent temperature resistance according to claim 1, characterized in that: The preparation method of polyester polyol is: The polyacid and the polyol are mixed in a mass ratio of (1-3):1, and an esterification reaction is carried out at 150-180°C for 1-3 hours, and then cooled to room temperature to obtain a polyester polyol.

4. The environmentally friendly PUR hot melt adhesive with excellent temperature resistance according to claim 1, characterized in that: The polyether polyol is at least one of tetrahydrofuran-propylene oxide copolymer glycol and polytetrahydrofuran ether glycol.

5. The environmentally friendly PUR hot melt adhesive with excellent temperature resistance according to claim 1, characterized in that: The isocyanate is at least one of diphenylmethane diisocyanate and hexamethylene diisocyanate.

6. The environmentally friendly PUR hot melt adhesive with excellent temperature resistance according to claim 1, characterized in that: The preparation method of modified isocyanate is: According to parts by mass, 350-400 parts of polyisocyanate, 10-12 parts of aminosulfonic acid, 0.15-0.2 parts of hydroxycarboxylic acid and 5-10 parts of tertiary amine are mixed, and reacted at 75-85° C. for 4-6 hours under nitrogen protection to convert into a clear modified isocyanate mixture; The polyisocyanate is at least one of toluene diisocyanate, isophorone diisocyanate and triphenylmethane triisocyanate; The aminosulfonic acid is at least one of 3-(cyclohexylamino)-1-propanesulfonic acid and 4-(cyclohexylamino)-1-butanesulfonic acid; The hydroxycarboxylic acid is at least one of 12-hydroxyoctadecanoic acid and 10-hydroxystearic acid; The tertiary amine is at least one of N,N-dimethylcyclohexylamine and N-methylpiperidine.

7. The environmentally friendly PUR hot melt adhesive with excellent temperature resistance according to claim 1, characterized in that: The chain extender is at least one of ethylene glycol, propylene glycol, 1,3-succinic acid and 1,4-cyclohexanedimethanol.

8. The environmentally friendly PUR hot melt adhesive with excellent temperature resistance according to claim 1, characterized in that: The preparation method of the anti-aging additive is: Cerium dioxide, titanium dioxide and zinc oxide are mixed to obtain a mixture, wherein the mass ratio of cerium dioxide, titanium dioxide and zinc oxide is (3-5):(0.8-1.2):1, the mixture is added into a hydrochloric acid solution with a mass concentration of 1-3%, ground in a ball mill for 2-4 hours, filtered and dried to obtain an activated mixture; The activated mixture is mixed with N-(2-aminoethyl)-3-aminopropyltrimethoxysilane and ethanol, wherein the mass ratio of the activated mixture, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane and ethanol is 1:(0.03-0.05):(5-10), reacted at 40-50° C. for 3-5 hours, filtered and dried to obtain a modified mixture; According to parts by mass, 5 to 10 parts of the modified mixture, 40 to 50 parts of maleimide monomer and 40 to 50 parts of bisphenol A epoxy resin are dissolved in 100 to 120 parts of butanone, reacted at 110 to 150° C. for 2 to 5 hours, and the butanone was evaporated under reduced pressure at 60 to 80° C. to obtain an anti-aging additive; The maleimide monomer is at least two of N-phenylmaleimide, N-(2-methylphenyl)maleimide, N-(4-methylphenyl)maleimide, N-(2,6-dimethylphenyl)maleimide, bis(4-maleimidophenyl)methane, and 2,2-bis(4-(4-maleimidophenoxy)-phenyl)propane.

9. A method for preparing an environmentally friendly PUR hot melt adhesive with excellent temperature resistance according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) mixing polyester polyol, polyether polyol, isocyanate, modified isocyanate, chain extender and anti-aging additive uniformly, conveying to a twin-screw extruder for heating reaction, the temperature of the twin-screw extruder is 220-250° C., and granulating in water, the temperature of the water is 5-15° C., to obtain polyurethane granules; (2) Drying the polyurethane particles at 70-80° C. to obtain PUR hot melt adhesive.

10. The use of an environmentally friendly PUR hot melt adhesive with excellent temperature resistance according to any one of claims 1 to 8, characterized in that: PUR hot melt adhesive is used in the automotive industry, furniture manufacturing, electronic products, packaging products, textiles and clothing, and medical devices.

Citation Information

Cited By

  • Green environment-friendly antibacterial polyurethane adhesive and synthesis method thereof

    CN120005550A

  • Environment-friendly PUR hot melt adhesive and preparation method thereof

    CN120988634A